BANKS' LOAN PORTFOLIO QUALITY MANAGEMENT - Gaybullaev Rakhim Murodovich (Scholar Express Journals, 2022)
In this article, theoretical views on the credit portfolio of commercial banks, methods of increasing the efficiency of managing the quality of the credit portfolio of commercial banks, analysis of quality management methods and thus the development of the lending system are studied
Keywords: commercial banks; credit; credit portfolio quality management; assessment